STRATEGY TO IMPROVE MSME PRODUCT BRANDING THROUGH DIGITAL MARKETING IN THE 5.0 ERA - Satriadi, Satriadi; Salsabila, Frysilia; Yuwanda, Fernanda; Azizah, Rijki Nur; Wan Mohd Yunus, Wan Mohd Azam (Jurnal Apresiasi Ekonomi, 2024)
There have been significant changes in economic life, business and trade in the era of Society 5.0. The presence of digital transformation in society has marked significant changes in business and trade activities. In order to survive and compete with many competitors, entrepreneurs need to implement HR development strategies to increase their competitiveness, one of which is by integrating their business with digital technology innovation. The aim of this research is to find out the right strategy to increase MSME product branding to increase the competitiveness of MSME product branding through digital marketing in the 5.0 era. This research uses a qualitative descriptive method, with data collection using the literature study method from various literature and relevant data related to the research topic. The research results show that the strategy for increasing MSME product branding that is needed to maximize the competitiveness of MSMEs in the 5.0 era is related to the ability to operate digital technology, as well as implementing creative and innovative marketing strategies through the use of digital technology, such as social media. media and websites to support MSME business activities and maximize their competitive advantages. Keywords: Strategy, Competitiveness, MSMEs, Human Resource Keywords: Strategy, Competitiveness, MSMEs, Human Resource